Advantages of thin single-photon avalanche diodes - Tan, S. L.; Ong, D. S.; Yow, H. K. (WILEY-V C H VERLAG GMBH, 2007)
The breakdown characteristics and timing jitter of thin and thick GaAs single-photon avalanche diodes are analyzed using a random ionization path length model. The larger relative dead space in thin devices is found to increase the sharpness of breakdown probability curves. Thin devices also produce lower timing jitter as a result of larger feedback ionization at high fields and weak dependence of jitter on dead space. Thus, if the dark count rate associated with higher electric field can be compensated, then thin devices may offer better performance in terms of faster breakdown and lower timing jitter, in addition to the known benefits of shorter detector dead time and velocity overshoot effects.(c) 2007 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.